Integrative Versus Distributive Bargaining: Choosing a Problem Resolution Process - Coleman, Rick; Fraser, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This paper examines the antithetical nature of two methods of resolving conflict through negotiation, and suggests there is an appropriate process depending upon how a party views the problem, and how he perceives it being viewed by his opponent.